Eriosoma Lanigerum Hausm Juice Damage Properties And Effects Of Entomophagy Against It (Texas Journal of Multidisciplinary Studies, 2022)
The article focuses on the biological control of fruit tree pests, which are currently a serious problem. This article examines the seasonal development of E. Lanigerum sap, life cycle, population density, effect on apple seedlings, yield reduction, Aphelinus mali, and Coccinellids, which are relatives of this pest, and their degree of exposure.